Leveraging Cultural-Historical Activity Theory (CHAT) in Education: Navigating the Globalized Digital Era - Ikeda, Osamu; Binarkaheni, Suyik (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2024)
The rapid development of digital technology around the world has significantly transformed education, influencing how knowledge is produced, disseminated, and consumed globally. This paper explores the application of Cultural-Historical Activity Theory (CHAT) within education, emphasizing its potential to navigate the complexities and opportunities presented by the digital era. CHAT, grounded in the works of Vygotsky and expanded by Engeström, provides a comprehensive framework for understanding the interplay between cultural artifacts, tools, and social interactions in educational settings. This theoretical approach is particularly relevant in analyzing how digital tools mediate learning processes, reshaping pedagogical practices and learning outcomes. Through a thorough review of existing literature and case studies, this paper highlights CHAT's role in fostering adaptive, culturally responsive, and technologically integrated educational environments worldwide. Furthermore, it identifies gaps in current research, particularly concerning the systematic study of digital technology's impact on educational activity systems and the effectiveness of CHAT-based interventions. By integrating key concepts of CHAT with contemporary digital tools, this paper contributes to the discourse on educational innovation, offering insights into the dynamic relationship between technology, pedagogy, and student engagement in education.